Proyecto especial para Haïti - Prophéte, Emmanuel (1990)
UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Agroalimentarias::Estación Experimental Agrícola Fabio Baudrit Moreno (EEAFBM)